Consistency of Merdeka Curriculum Towards the Profile of Pancasila Students at the Various Education Levels: A Contextual Study - Gulyanto, Bambang; Sambayu, Harry; Sepristiwanto , Muhammad; Panjaitan, Gita Sabina Putri; Az Zahra, Cindy Purnama Sari (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
There are various perspectives on the consistency of the Merdeka Curriculum Towards Pancasila profiles at various eds that still need to impact learner efficacy. This article discusses and examines the consistency of the Merdeka Curriculum towards Pancasila Profiles at Various Education Levels. This article used a theoretical study based on a qualitative and quantitative approach. This approach prioritizes theoretical studies, articles, and other sources that are considered very relevant to the discussion. The discussion method uses five levels: In-depth description, holistic approach, qualitative analysis, use of primary data, and limited data generalization. Meanwhile, the quantitative approach uses a questionnaire distribution with 57 items and involves 45 respondents using purposive random sampling. Based on the study of this article, it was found that curriculum consistency Towards the Profile of Pancasila Students at the education level can be categorized as high, with an average score of 75.5. It could be done by prioritizing various positive perspectives to develop a specific ability to achieve the Golden Indonesia in 2045 goal. This research implies that it can be the solution alternative for making future education decisions.